Immunotherapy, Tumor Microenvironment and Survival Signaling - Golubovskaya, Vita (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book is based on the Cancers journal Special Issue entitled "Immunotherapy, Tumor Microenvironment and Survival Signaling", and focuses on important problems concerning tumors and tumor microenvironment interactions, as well as novel immunotherapies such as CAR-T cell therapy. Immunotherapies have recently shown remarkable results in the treatment of cancer patients. However, there are still many questions that remain to be solved in regards to more effective therapies, such as the tumor heterogeneous profile, tumor microenvironment, and tumor survival epigenetic and genetic pathways, all of which make patients resistant to the presently available treatments for cancer. This book demonstrates different approaches to overcome the challenges faced by immunotherapies due to suppressive tumor microenvironments. This book includes 18 papers that can be divided into three chapters: 1. novel immunotherapies; 2. targeting tumor microenvironment and novel approaches; 3. targeting tumors and tumor microenvironment in different types of cancer.